Reformulações para o problema integrado de dimensionamento e sequenciamento da produção - Maldonado, Michelli [UNESP] (2015)
Operational Research has become an ally of several real problems, especially problems of industry, whose objective is to minimize their costs. One of the problems of many managers is to determine how much to produce, when to produce and in what order produce. To answer these three questions simultaneously simply solve the integrated problem of lot sizing and sequencing of production. This work presents mathematical models that can be adapted in several case studies to answer the threefold question: how much, when and in what order, all while minimizing inventory costs, delay and return. This thesis is interested on the question, What is the best model for the integrate lot sizing and scheduling problem?. ItWere proposed five models and theys were studied in the theoretical and computational viewpoint. All models was based in the travelling salesman problem (TSP). And the results show that the integrate lot sizing and scheduling problem based in the TSP isn't the same model for the TSP